ANALISIS HASIL PELATIHAN 2024 di PPSDM KEBTKE DAN STRATEGI PENGUATAN KOMPETENSI ASN MENUJU NET ZERO EMISSION 2060 - Bagus Rizky Dewantoro; Rika Widiastuti Siregar; Rifka Sofianita (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2025)
This study aims to evaluate the effectiveness of the training programs organized by PPSDM KEBTKE in 2024 and their strategic alignment with Indonesia’s Net Zero Emissions (NZE) 2060 target. Using a mixed-methods approach—qualitative and quantitative analyses—the qualitative analysis was conducted to assess the thematic alignment between the training programs and priority sectors of the energy transition, while the quantitative analysis employed multiple linear regression to measure the impact of nine training variables on participants’ competency improvement. The results show that 90% of the training directly supported NZE priority sectors, while the remaining 10% still contributed indirectly to human resource preparedness. Statistically, three variables were found to have a significant effect on competency improvement: training schedule and duration, cleanliness of public facilities, and completeness of learning facilities. These findings provide an empirical basis for designing effective training strategies that are in line with national energy policies.